(3GdYdGeI GdJLGQjI (B:s (3GdeGgjI hGdGgejI (B/s - (3ghGQj, eYQGLs; (3SGLj, eUWai s ((3YeGf(B: s (3OGQ cfhR GdeYQaI GdYdejI ddfTQ hGdJhRjY(B, s, 2013)
(3GdYdGeI eaGgje CSGSjI(B- (3bQGQGJ GdYdGeI(B- (3CfhGY GdYdGeGJ GdJLGQjI(B- (3EfTGA GdYdGeI GdJLGQjI hOhQI MjGJgG(B- (3GSJQGJjLjGJ Ndb hHfGA GdYdGeI(B- (3HfGA hJSLjd GdYdGeI hMeGjJgG(B- (3MeGjI GdYdGeI GdJLGQjI(B- (3GdhdGA ddYdGeI GdJLGQjI(B- (3JfejI GdhdGA ddYdGeI GdJLGQjI(B- (3GdJShjb GdOGNdj h JfejI GdhdGA ddYdGeI GdJLGQjIs
(3bGFeI GdeQGLY U(B.211s
Keywords: (3GdESe GdJLGQjs; (3GdJShjbs; (3GdYdGeGJ GdJLGQjIs